(3TQM GdTGajIs - (3eLghds ((3QeVGf Hf eUWai Hf jYbhH s)
(3ChdgG (B:s
(3GYde Cf GdJUQja ai GddZI GdJZjQ Cbhd GYde CeQ ef Yde s
(3BNQgG (B:s
(3Je GdcJGH HYhf Gdedc GdhgGH hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdTGajI ai GdUQa dGHf GdMGLHs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdUQas